Роль жандармів у забезпеченні наступальних операцій (правозастосовна практика) - Бернадський, Б. Bernadskyi B. (СНУ ім. Лесі Українки, 2018)
У статті, на прикладі Волинського губернського жандармського управління, розглядаються зміни функцій та основні напрямки діяльності підрозділу політичної поліції в умовах воєнного часу, передусім, в період активізації бойових дій – наступальної операції військ Південно-Західного фронту навесні-влітку 1916 р. Жандармські структури у прифронтовій смузі відігравали допоміжну роль, зосередившись на загальному нагляді, провадженні дізнань та виконанні функцій воєнної поліції. Жандармські структури також повернулись до контррозвідувальної роботи.The article considers the changes in the functions and main directions of the political police units activity under the conditions of wartime in the Volyn Huberniya. The author focuses attention on the main features of the activities of the Volyn Huberniya gendarme department in the time of the fighting operations aggravation. The spring-summer military operation of the South-Western Front, which went down into history as the Brusilov Breakthrough, was chosen as the most vivid example of such aggravation. By 1916 the illusion of class peace, which loomed at the beginning of the war, had finally vanished. However, the ruling strata of the Russian Empire began to link the plan for victory in the war with the traditional struggle not only against the revolutionary movement, but also against opposition. These factors predetermined the redistribution of the functions and activities of the political police investigation bodies. At the same time, according to the logic of the events in the front-line zone, the leading role in the investigation was transferred to the military intelligence agencies, which finally turned into the political police. Under these conditions the gendarme authorities began to play a supporting role, in fact performing the functions of the military police.
Role of Gendarmes in the Attack Operations (Law Enforcement Practice)
Keywords: Брусіловський прорив; Волинське ГЖУ; політичний розшук; жандарми; контррозвідка; Brusilovskyi breakthrough; Volyn GZHU; political investigation; gendarmes; counterintelligence